2007
DOI: 10.1186/2046-0481-60-12-728
|View full text |Cite
|
Sign up to set email alerts
|

Resistance studies of erythromycin and rifampin for Rhodococcus equi over a 10-year period

Abstract: This study sought to determine whether an increase in resistance of Rhodococcus equi to the antibiotics rifampin and erythromycin occurred over a 10-year period. This was carried out by the use of E test strips for rifampin and erythromycin to determine the MIC (minimum inhibitory concentration) values of Rhodococcus equi to this combination of antibiotics.The findings of this study indicated that there was an increase in resistance of Rhodococcus equi to rifampin and erythromycin over the 10-year period. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
(24 reference statements)
1
25
1
2
Order By: Relevance
“…Treatment of R. equi infection must be based on the results of antimicrobial susceptibility tests because there is no standard drug regimen for R. equi infection in humans (Roda et al 2009) and the emergence of some strains resistant to various antibiotics has been reported within the last 10 years (Buckley et al 2007). R. equi isolates in our study showed resistance to β-lactam agents, in agreement with the results described by Roda et al (2009).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Treatment of R. equi infection must be based on the results of antimicrobial susceptibility tests because there is no standard drug regimen for R. equi infection in humans (Roda et al 2009) and the emergence of some strains resistant to various antibiotics has been reported within the last 10 years (Buckley et al 2007). R. equi isolates in our study showed resistance to β-lactam agents, in agreement with the results described by Roda et al (2009).…”
Section: Discussionsupporting
confidence: 82%
“…Interpretation categories beta-lactamase inhibitor, the activity was significantly increased (98.04% for amoxicillin-clavulanate), confirming the correlation of β-lactamase enzyme production and resistance. Because R. equi is an intracellular bacteria, the infection can be treated with macrolides, such as erythromycin and rifampicin (Heidmann et al 2006, Buckley et al 2007). The macrolides tested in our study, azithromycin and clarithromycin, were 100% effective, while erythromycin was 98% effective against the R. equi isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Buckley et al (10) highlighted a 2-fold increase in MICs over a 10-year period. Moreover, the emergence of rhodococci resistant to these antibiotics has already been reported in humans and animals (2,7,10,28). This suggests that there may be a problem in the treatment of R. equi infection, and new effective broad-spectrum drugs will be needed in the near future.…”
mentioning
confidence: 99%
“…Since then, R. equi resistance to these drugs has been observed (BUCKLEY et al, 2007). In this respect, azithromycin (AZM) and clarithromycin (CLR) have been proposed as alternatives to ERY for the treatment of R. equi infections in foals (JACKS et al, 2003).…”
mentioning
confidence: 99%
“…In vitro, R. equi has to be sensitive to a wide variety of antibiotics, such as aminoglycosides, beta-lactams and second-generation of cephalosporins (GIGUÈRE et al, 2010). However, their ability to replicate in macrophages and neutrophils limited the therapeutic options to drugs able to penetrate in lipophilic environment (BUCKLEY et al, 2007).…”
mentioning
confidence: 99%